2008
DOI: 10.2298/sarh0808391m
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of spa treatment on functional status and quality of life of patients with rheumatoid arthritis

Abstract: Balneotherapy, together with climatic factors in Igalo, leads to a significant improvement of functional status and quality of life in patients suffering from RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The Journal of Nutrition, Health & Aging© Volume 13, Number 9, 2009 Several studies reported that spa care was beneficial for the mental state of the patients (92,93) and for their quality of life (94)(95)(96). It is also admitted that it brings benefit during pain treatment especially in arthrosis, often reported in elderly population (94)(95)(96)(97)(98).…”
Section: Balneotherapy Prevention Of Cognitive Decline and Care The mentioning
confidence: 99%
See 1 more Smart Citation
“…The Journal of Nutrition, Health & Aging© Volume 13, Number 9, 2009 Several studies reported that spa care was beneficial for the mental state of the patients (92,93) and for their quality of life (94)(95)(96). It is also admitted that it brings benefit during pain treatment especially in arthrosis, often reported in elderly population (94)(95)(96)(97)(98).…”
Section: Balneotherapy Prevention Of Cognitive Decline and Care The mentioning
confidence: 99%
“…It is also admitted that it brings benefit during pain treatment especially in arthrosis, often reported in elderly population (94)(95)(96)(97)(98).…”
Section: Balneotherapy Prevention Of Cognitive Decline and Care The mentioning
confidence: 99%
“…Romatoid artritte radonlu ve karbondioksitli banyoların etkinliğinin kıyaslandığı bir çalışmada her iki banyo türünde de ağrı düzeylerinde ve fonksiyonel durumda iyileşme olduğu belirtilmiştir (14). Mustur ve arkadaşlarının romatoid artritte balneoterapinin etkinliğini araştırdıkları çalışmada mHAQ ve SF-36 skorlarında düzelme olduğu belirtilmiştir (15). Stojanovic ve arkadaşlarının romatoid artritte de fizik tedavi yöntemleri ile kombine olarak balneoterapi kullanılmasının DAS28 skorlarında ve yaşam kalitesi parametrelerinde düzelme sağladığı belirtilmiştir (16).…”
Section: Discussionunclassified